2019
DOI: 10.1159/000500063
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Profiling of Circular RNA Identifies hsa_circ_0126991 as a Potential Risk Factor for Essential Hypertension

Abstract: Essential hypertension (EH), a major cause of cardiovascular diseases, is an important public health issue. However, the molecular mechanisms involved in EH remain unknown. Circular RNA (circRNA) is a novel promising biomarker for the disease. The purpose of the present study was to determine the expression of circRNAs in the blood of EH patients and to evaluate the performance of circRNA for early diagnosis of EH. A total of 178 subjects were recruited in the case-control study. Initial screening was done by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Additionally, five circRNAs, namely hsa_circ_0105130, hsa_circ_0109569, hsa_circ_0072659, hsa_circ_0079586, and hsa_circ_0064684, have been identified as being associated with essential hypertension [55]. Other circRNAs such as hsa_circ_0126991, hsa_circ_0014243, and hsa_circ_0037909 have also been recognized as potential biomarkers for essential hypertension [51,56,57]. Mechanistically, circRNAs can impact cardiovascular function by regulating the expression of transcription factors, microRNAs, and proteins, thereby influencing the development and progression of hypertension [58,59].…”
Section: Research Status Of Lncrnas and Circrnas In Cvd Hypertensionmentioning
confidence: 99%
“…Additionally, five circRNAs, namely hsa_circ_0105130, hsa_circ_0109569, hsa_circ_0072659, hsa_circ_0079586, and hsa_circ_0064684, have been identified as being associated with essential hypertension [55]. Other circRNAs such as hsa_circ_0126991, hsa_circ_0014243, and hsa_circ_0037909 have also been recognized as potential biomarkers for essential hypertension [51,56,57]. Mechanistically, circRNAs can impact cardiovascular function by regulating the expression of transcription factors, microRNAs, and proteins, thereby influencing the development and progression of hypertension [58,59].…”
Section: Research Status Of Lncrnas and Circrnas In Cvd Hypertensionmentioning
confidence: 99%
“…Hypertension is a systemic disease, and its complex pathogenesis makes it difficult to elucidate the precise molecular mechanisms involved. Numerous studies have demonstrated that circRNAs are potential biomarkers and important modulators in hypertension ( Liu et al, 2017 ; Wu et al, 2017 ; Bao et al, 2018 ; Liu et al, 2019a ; Zheng et al, 2019 ; Lu et al, 2020 ; Yin et al, 2020 ; Zheng et al, 2020 ; He et al, 2021 ; Tao et al, 2021 ). CircRNA array analysis of blood samples obtained from patients with essential hypertension and healthy individuals showed that the expression of circRNAs was significantly different between these groups.…”
Section: Ev-circrnas Are Involved In As Risk Factorsmentioning
confidence: 99%
“…We previously analyzed peripheral blood circRNAs between 5 diagnosed EH patients and 5 healthy controls using a microarray analysis and we found a total of 287 circRNAs were differentially expressed between the two groups including 209 up-regulated circRNAs and 78 down-regulated circRNAs. 13 For subsequent functional analysis to obtain the potential biomarkers for clinical application, the circRNAs were selected from the up-regulated exonic circRNAs (ecircRNAs) using the following filtering criteria: fold change >2.0 and P < .01. Then, hsa_circ_0093587 and hsa-circRNA9102-5 were included in this study.…”
Section: Candidate Circrnas and Their Target Mirnas Predictionmentioning
confidence: 99%